Analysis of Work Stress among Faculties and Coping Strategies at Private Institutions in Mathura District (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2017)
In the current scenario of stiff competition, Stress is inevitable in all walks of human life. The phenomenon of work stress among faculties of private institutions has been receiving increased global attention and concern in recent years. Teaching has now become a very demanding occupation with a lot of stresses for a teacher who has a lot of deadlines to meet and a lot of responsibilities to shoulder besides teaching a child what are in a text book. There is a continuous change in social, cultural, economic, political, legal and technological environment. Stress at workplace can lead to problems for the individual, working relationships and the overall environment. This results in lowered self esteem and poor concentration skills for the employees. Managing stress in the workplace is therefore an essential part of both individual and it is institutional social responsibility also. This study investigated causes of stress and coping strat
Keywords: Work stress; Causes; Coping strategies